Encouraging the learning of hydraulic engineering subjects in agricultural engineering schools - Sinobas, Leonor Rodríguez; Sánchez Calvo, Raúl (European journal of engineering education, 2014)
Several methodological approaches to improve the understanding and motivation of students in Hydraulic Engineering courses have been adopted in the Agricultural Engineering School at Technical University of Madrid. During three years student's progress and satisfaction have been assessed by continuous monitoring and the use of 'online' and web tools in two undergraduate courses. Results from their application to encourage learning and communication skills in Hydraulic Engineering subjects are analysed and compared to the initial situation. Student's academic performance has improved since their application, but surveys made among students showed that not all the methodological proposals were perceived as beneficial. Their participation in the 'online', classroom and reading activities was low although they were well assessed.